2022
DOI: 10.1186/s12909-022-03630-1
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of an evidence-based model of feedback implemented on an undergraduate dental clinical learning environment

Abstract: Objectives Dental graduates must graduate with high levels of clinical skills. Education in the clinical environment needs to be more than didactic supervision of practice by clinical teachers. Appropriate feedback in this context, is therefore critical to the development of student competence and confidence. This study was conducted to enhance and develop the assessment and feedback processes during clinical sessions in a Dental University Hospital in an effort to contribute to the development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…A great deal of data has highlighted the importance of using appropriate guidance (evaluation sheets), which should preferably be standardized, to improve self-assessment 12 . A study that aimed to evaluate a newly developed evidence-based model of feedback (MOF) featuring six key steps pertaining to patient safety showed that the introduction of this model resulted in effective feedback even in complex and challenging situations 13 .…”
Section: Introductionmentioning
confidence: 99%
“…A great deal of data has highlighted the importance of using appropriate guidance (evaluation sheets), which should preferably be standardized, to improve self-assessment 12 . A study that aimed to evaluate a newly developed evidence-based model of feedback (MOF) featuring six key steps pertaining to patient safety showed that the introduction of this model resulted in effective feedback even in complex and challenging situations 13 .…”
Section: Introductionmentioning
confidence: 99%
“…In order to perform dental procedures, a dentist must be able to work with precision on an extremely small scale. This requires exceptional hand–eye coordination to ensure the safety of patients and proficiency in many different instruments [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%